Islamic Educational Values in the Patuq Tradition - Erlan Muliadi; Abdul Haris Rasyidi; Ulyan Nasri (Al-Hayat: Journal of Islamic Education, 2024)
This study examines the values ​​of Islamic religious education in a tradition called Patuq which is carried out after the death ceremony. With a qualitative approach and case study type, this research was conducted. Data were obtained from primary sources in the form of community leaders and family members, while supporting data were obtained from experts who are familiar with Lombok culture and religious institutions. The data collection used observation, interview and documentation techniques. While the analysis used the Miles and Huberman model. For data validity, triangulation of sources and methods was used. The results of this study show the values ​​of Islamic education in the Patuq tradition including; Shadaqah values, cooperation and solidarity, respect for the deceased, holiness and purity. The moral lessons that can be learned from this tradition are Patience, Obedience, Togetherness, Gratitude, Simplicity, and Self-Control. Each of these values ​​contributes to the development of character and spiritual understanding of the community, in line with broader Islamic teachings. Research on the Patuq tradition highlights the integration of social and cultural values ​​in Islamic education. This approach emphasizes cooperation, community involvement, and the importance of charitable practices. By connecting religious teachings with local customs, educators can strengthen students’ cultural and religious identities while promoting empathy and social responsibility. This approach encourages collaborative learning, deepens understanding of the afterlife, and instills values ​​of cleanliness and purity, as well as fostering well-rounded individuals who embody Islamic ethics in their interactions.